Small molecule p300/catenin antagonist enhances hematopoietic recovery after radiation - Zhao, Yi; Wu, Kaijin; Nguyen, Cu; Smbatyan, Goar; Melendez, Elisabeth; Higuchi, Yusuke; Chen, Yibu; Kahn, Michael (PLOS ONE, 2017)
There is currently no FDA approved therapeutic agent for ARS mitigation post radiation exposure. Here we report that the small molecule YH250, which specifically antagonizes p300/catenin interaction, stimulates hematopoiesis in lethally or sublethally irradiated mice. A single administration of YH250 24 hours post irradiation can significantly stimulate HSC proliferation, improve survival and accelerate peripheral blood count recovery. Our studies suggest that promotion of the expansion of the remaining HSC population via stimulation of symmetric non-differentiative proliferation is at least part of the mechanism of action.